Mengoptimalkan Kebutuhan Gizi Balita dengan Metode Simpleks Menggunakan POM-QM untuk Pencegahan Stunting - Nurrochmah Sri Rahayu; Saluky; Nurrochmah , Nurrochmah Sri Rahayu (Perspectives in Mathematics and Applications, 2025)
This research aims to develop an optimization mathematical model to help meet toddlers' daily nutritional intake needs to prevent stunting. The Simplex method is applied in this model to determine food combinations that meet the standards of nutritional needs at minimal cost, considering budget constraints and the availability of foodstuffs so that they can be adapted to diverse socioeconomic conditions. The POM-QM application is used as a calculation tool to apply the Simplex method, making the optimization process more practical and accurate. Mathematical modeling is carried out by compiling a function of objectives by minimizing the cost of consuming foodstuffs that meet the daily nutritional needs of toddlers, including protein, fat, carbohydrates, iron, vitamin A, and vitamin C. The optimization results showed that nutritional needs could be optimally met with a combination of vegetable soup consumption of 22.5 grams, Tempe 8.476 g, and banana 4.5 g, with a total minimum cost of IDR 146,928. The nutrient content of the combination exceeds daily needs, such as protein (241.41 g), fat (274.06 g), Fe (82.93 mg), as well as vitamin A (450 RE) and vitamin C (45 mg), while carbohydrates are fulfilled exactly as much as 220 grams. These results show that the optimization approach can be used to design a balanced, nutritious diet that is cost-efficient as an effort to prevent stunting in toddlers.